PAGAMENTO POR SERVIÇOS AMBIENTAIS: A POLITICA PÚBLICA DO PROGRAMA BOLSA VERDE - Novak, Maricléia Aparecida Leite (2017)
This research had the purpose of studying the operationalization of a public policy of Payments for Environmental Services, concretized in the form of the Bolsa Verde Program (PBV), executed on the initiative of the Brazilian government. The study was conducted in a qualitative way with the data collection carried out in four Agrarian Reform settlements, located in the area covered by a Conservation Unit of sustainable use, in the center-south region of the state of Paraná. The objectives of the study were to analyze the PBV under the perspective of its effectiveness as an initiative to encourage environmental preservation practices and as an initiative to eradicate rural poverty. The data collected led to the conclusion that, although PBV, primarily focused on environmental preservation, the modus operandi of its implementation only makes it effective as a policy to eradicate rural poverty.